Skills readiness on Industrial Revolution 4.0 among undergraduate students at STML - Rohizat, Nur Dalila; Mohd Zahari, Fadhilah (Universiti Utara Malaysia, 2020)
The purpose of the paper is to examine the skills readiness on Industrial Revolution 4.0 among undergraduate students. Besides, this study aims to identify the extent of their awareness on Industrial Revolution 4.0 when graduates and perceived importance of skills readiness to embrace Industrial Revolution 4.0. Using quantitative method, 100 final year STML students were chosen as the respondents to answer the questionnaire survey. Then, data analysis was performed using descriptive analysis. The result shows that the students are highly aware on IR4.0 but they are not really prepared in terms of skills even they know that is important for their future. Thus, students, university, and also industry need to take action about the importance of IR4.0. It is hoped that the findings of this study will serve as a platform for future research in preparing the students to embrace IR4.0 effectively.